Sales Information System of Mobile Marketing at PT. World Innovative Telecommunication Using Up Selling, Cross Selling and Down Selling Methods - Eva Eva; Benny Daniawan; Aditiya Hermawan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
In the era of globalization the development of information system technology is very rapidly evolving and very affecting PT. World Innovative Telecommunication engaged in retail, namely mobile phones. Pt. World Innovative Telecommunication still does not have an online marketing and sales system that makes it difficult for consumers to know the products sold. The purpose of this system was to help PT. World Innovative Telecommunication in marketing, selling and increasing sales by using up selling, cross selling and down selling methods and providing convenience for consumers to get information about products sold as well as increase consumer satisfaction by using systems created and covered to unreachable areas.